Reasons for Thiomicrospira crunogena's recalcitrance towards previous attempts to detect its hydrogen consumption ability. Issue 1 (21st December 2015) - Hansen, Moritz; Perner, Mirjam
Summary: The first T hiomicrospira species was isolated in 1972 and was described as a sulfur‐oxidizing chemolithoautotroph. Since then, several other Thiomicrospira species have been recovered from around the globe and have been classified as common sulfur oxidizers. In the past, attempts to demonstrate hydrogen consumption of a T hiomicrospira species have failed. However, recently, we showed that some Thiomicrospira strains can indeed consume hydrogen. Here, we discuss why T hiomicrospira species have likely resisted efforts to consume hydrogen under the offered conditions. It appears that their hydrogen consumption ability is closely tied to the concentration of nickel in the medium. Investigated carbonate and thiosulfate concentrations did not appear to be critical for hydrogen utilization under the tested conditions.